Macular corneal dystrophy and associated corneal thinning - Dudakova, L; Palos, M; Svobodova, M; Bydzovsky, J; Huna, L; Jirsova, K; Hardcastle, A J; Tuft, S J; Liskova, P (Eye (London, England), 2014)
PURPOSE: To identify the molecular genetic cause of macular corneal dystrophy (MCD) in four probands, and characterize phenotypic similarities between MCD and keratoconus. METHODS: We performed ophthalmological examination, Scheimpflug imaging (Pentacam, Oculus Inc.), histopathological examination of excised corneal buttons, and direct sequencing of the CHST6 coding region. RESULTS: Pentacam measurements were taken in six eyes of three probands. All showed diffuse corneal thinning with paracentral steepening of the anterior corneal surface that was graded as keratoconus by the integrated software, but without associated ectasia of the posterior corneal surface or regional thinning. Homozygous or compound heterozygous CHST6 mutations were identified in all cases, including two novel mutations, c.13C>T; p.(Arg5Cys) and c.289C>T; p.(Arg97Cys). DISCUSSION: Localized elevation of the anterior corneal curvature can occur in MCD in the absence of other features of keratoconus. The identification of a further two Czech probands with the compound allele c.[484C>G; 599T>G] supports the enrichment of this allele in the study population.
Keywords: mutace; dospělí; Corneal Dystrophies, Hereditary; Corneal Pachymetry; Female; Adult; ženské pohlaví; rohovka; Organ Size; Carbohydrate Sulfotransferases; Sulfotransferases; Corneal Topography; Adolescent; Cornea; lidé; Mutation; pachymetrie rohovky; dědičné dystrofie rohovky; velikost orgánu; Male; rohovková topografie; sulfotransferasy; mužské pohlaví; sulfotransferasy sacharidů; mladiství; Humans